2015
DOI: 10.1590/1806-9282.61.05.469
|View full text |Cite
|
Sign up to set email alerts
|

Clinical management of incidental findings on pelvic adnexal masses

Abstract: Summary Due to widespread use of pelvic and transvaginal ultrasound in routine gynecological evaluation, the incidental finding of adnexal masses has led to discussions about management in asymptomatic patients regarding the risk of ovarian cancer. Transvaginal ultrasonography remains the modality of choice in the evaluation of suspicious characteristics. The combined analysis of ultrasound morphological parameters with Doppler study, serum carcinona antigen 125 and investigation of a symptom index may improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Some cystic formations may be complex cysts with exfoliation, hemorrhage, or thick walls. Differential diagnosis between tumor-like, benign, and malignant ovarian lesions is quite difficult and transvaginal, and transabdominal ultrasonography becomes a tool of primary imaging [ 8 , 9 ]. According to the classification of the International Ovarian Tumor Analysis group, multilocular cysts with a solid component have the highest risk of malignancy [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some cystic formations may be complex cysts with exfoliation, hemorrhage, or thick walls. Differential diagnosis between tumor-like, benign, and malignant ovarian lesions is quite difficult and transvaginal, and transabdominal ultrasonography becomes a tool of primary imaging [ 8 , 9 ]. According to the classification of the International Ovarian Tumor Analysis group, multilocular cysts with a solid component have the highest risk of malignancy [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the frequent use of magnetic resonance imaging and computed tomography to characterize ovarian pathology, qualitative images of ovarian masses can be obtained using multiparametric ultrasonography, which is based on the use of standard B-mode, color Doppler mapping, energy and spectral Doppler mode and thus simplifying the process of diagnosing this pathology [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ovarian Cancer is the second most common gynecologic cancer worldwide and the sixth most common cancer in women (3) with approximately 255,000 new cases diagnosed each year (5). It has the highest mortality rate among gynecologic cancers with a general survival rate of less than 50% (8).…”
Section: Introductionmentioning
confidence: 99%
“…First-line imaging tool is ultrasonography, either transabdominal or transvaginal. 1,2 According to the classification of the International Ovarian Tumour Analysis Group, solid lesions or multilocular cysts with solid component have the highest risk of malignancy. 2 Imaging with conventional greyscale ultrasonography, Doppler ultrasonography and/or MRI is important for diagnosis before deciding about surgery.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 According to the classification of the International Ovarian Tumour Analysis Group, solid lesions or multilocular cysts with solid component have the highest risk of malignancy. 2 Imaging with conventional greyscale ultrasonography, Doppler ultrasonography and/or MRI is important for diagnosis before deciding about surgery. 1 It is reported that subjective evaluation of greyscale ultrasonography characteristics, colour and power Doppler imaging and three-dimensional Doppler imaging characteristics of the ovarian malignant and benign lesions might differ, and each modality has some advantages over the other.…”
Section: Introductionmentioning
confidence: 99%